2019
DOI: 10.1021/acsanm.9b02176
|View full text |Cite
|
Sign up to set email alerts
|

H5PV2Mo10O40 Polyoxometalate Encapsulated in NU-1000 Metal–Organic Framework for Aerobic Oxidation of a Mustard Gas Simulant

Abstract: The immobilization of H5PV2Mo10O40 polyoxometalates (POMs) in the in the mesoporous channel-type metal–organic framework (MOF), NU-1000, via simple impregnation method is reported here. Characterization of the composite PV2Mo10@NU-1000 activated by supercritical CO2 revealed that the POMs occupy the mesopore. Upon heating as low as 40 °C in the absence of bulk solvent, the POMs migrate to the micropore. However, the presence of solvent, such as cyclohexane, impedes this transformation. The material was active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 72 publications
3
64
0
Order By: Relevance
“…A bulky molecule, [Mg(OMe) 2 (MeOH) 2 ] 4 was incorporated in the mesopores of NU-1000 by o Gil-San-Millan et al 243 Due to their tendency to aggregate and instability in solutions, polyoxometalates (POMs) are one of the most studied species supported by NU-1000. 244 POMs are anionic metal oxide clusters composed of group V or VI transition metals having acid-base and redox properties. NU-1000 has been found as an appropriate support for POMs thanks to its small triangular channels (12 Å) enabling the incorporation of large POMs while the larger (31 Å) hexagonal channels promote the substrate diffusion.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…A bulky molecule, [Mg(OMe) 2 (MeOH) 2 ] 4 was incorporated in the mesopores of NU-1000 by o Gil-San-Millan et al 243 Due to their tendency to aggregate and instability in solutions, polyoxometalates (POMs) are one of the most studied species supported by NU-1000. 244 POMs are anionic metal oxide clusters composed of group V or VI transition metals having acid-base and redox properties. NU-1000 has been found as an appropriate support for POMs thanks to its small triangular channels (12 Å) enabling the incorporation of large POMs while the larger (31 Å) hexagonal channels promote the substrate diffusion.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Therefore, the selectivity of the reaction is highly important. Two different POMs, H 3 PW 12 O 40 and H 5 PV 2 Mo 10 O 40 , have been encapsulated in NU-1000 (named as PW 12 @NU-1000 245,247,248 and PV 2 Mo 10 @NU1000, 244 respectively) for the oxidation of CEES using hydrogen peroxide (H 2 O 2 ) as the oxidant. Results showed that while 100% conversion of the parent agent is successfully done, the problem is the selectivity toward the desired non-toxic oxidation product.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another Zr-based MOF, denoted as NU-1000, with small triangular (12 Å) and larger hexagonal (31 Å) channels, has been used to support POMs such as [PW12O40] 3− and [PMo10V2O40] 5− [85][86][87]. For example, Farha's group prepared PW12@NU-1000 through an impregnation method for the oxidation of 2-chloroethyl ethyl sulfide (CEES), using H2O2 as the oxidant.…”
Section: Oxidation Reactionmentioning
confidence: 99%
“…[17,18,[20][21][22] In light of good solubility of POMs in electrolyte due to their low specific surface area and poor stability, a number of POM-based materials have been constructed by assembly of POMs and organic ligands. [23][24][25][26] To the best of our knowledge, the suitable organic ligands can not only improve the stability of POM-based materials, [11] but also endue them tunable structures. [27,28] For example, the reported organic ligand containing multi-chelating groups, 4-(pyridin-2-yl)pyrimidine-2-thiolate groups, are easy to chelate with metal ions, which are beneficial to improve their stability.…”
Section: Introductionmentioning
confidence: 99%